Biocompatible and biodegradable alginate/poly(N‐isopropylacrylamide) hydrogels for sustained theophylline release. Issue 17 (9th April 2014) - Dumitriu, Raluca Petronela; Oprea, Ana‐Maria; Natalia Cheaburu, Catalina; Nistor, Manuela‐Tatiana; Novac, Ovidiu; Ghiciuc, Cristina Mihaela; Profire, Lenuta; Vasile, Cornelia
ABSTRACT Mixed‐interpenetrated polymeric networks based on sodium alginate (ALG) and poly(N‐isopropylacryl amide) (PNIPAAm) covalently cross‐linked with N, N'‐methylenebisacrylamide are studied for their biocompatibility, nontoxicity, and biodegradability aiming their application in drug delivery. The presence of drug‐polymeric matrix interactions and the distribution of the drug in the polymeric network for theophylline‐loaded ALG/PNIPAAm hydrogels are also investigated by spectroscopic and microscopic methods. The quantitative evaluation of theophylline loaded hydrogels performed by NIR‐CI technique shows a better drug entrapment and a higher homogeneity of the samples with increased alginate content. The thermal behavior of the hydrogels is significantly modified by theophylline presence. The application of the ALG/PNIPAAm hydrogels as carriers for sustained drug release formulations was assessed by the theophylline release tests performed both by in vitro and in vivo studies. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40733.